2020
DOI: 10.1111/eea.12964
|View full text |Cite
|
Sign up to set email alerts
|

Monarda fistulosa hydrolate as antimicrobial agent in artificial media for the in vitro rearing of the tachinid parasitoid Exorista larvarum

Abstract: Exorista larvarum (L.) (Diptera: Tachinidae), a larval parasitoid of Lepidoptera, can be reared from egg to fecund adult on artificial media composed of crude components. The standard in vitro culture is performed in 24-well plastic rearing plates. Exorista larvarum eggs, removed from superparasitized larvae of Galleria mellonella (L.) (Lepidoptera: Pyralidae), are individually placed in the wells, each containing a cotton swab soaked in liquid medium. The plates are then sealed until parasitoid puparium forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Numerous European countries have been cultivating M. fistulosa as an aromatic plant. Studies have shown that M. fistulosa is rich in biologically active substances, making it a great source of EOs (Dindo et al, 2020). Furthermore, studies have proven that the EOs and hydrolates from M. fistulosa exhibit high activity against pathogenic microorganisms and can be used in humans and plants (Dindo et al, 2020).…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous European countries have been cultivating M. fistulosa as an aromatic plant. Studies have shown that M. fistulosa is rich in biologically active substances, making it a great source of EOs (Dindo et al, 2020). Furthermore, studies have proven that the EOs and hydrolates from M. fistulosa exhibit high activity against pathogenic microorganisms and can be used in humans and plants (Dindo et al, 2020).…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…Studies have shown that M. fistulosa is rich in biologically active substances, making it a great source of EOs (Dindo et al, 2020). Furthermore, studies have proven that the EOs and hydrolates from M. fistulosa exhibit high activity against pathogenic microorganisms and can be used in humans and plants (Dindo et al, 2020). Some of the major constituents found in M. fistulosa, such as carvacrol, γ-terpinene, geraniol, rosmarinic acid, and thymol, as well as the presence of thymol and carvacrol in the EOs of M. fistulosa, enable the extract to pose antibacterial and antihelmintic properties (Mattarelli et al, 2017).…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the major components of an EO may not be the same present in the corresponding HY. However, several HYs possess antimicrobial and antifungal activity [ 33 , 35 , 36 , 37 , 38 , 39 ], but only a few studies have investigated their insecticidal action. Petrakis and colleagues [ 40 ] examined the possible use of HYs from Origanum majorana L., Mentha pulegium L., and Melissa officinalis L. against Myzus persicae Sulzer, showing that they altered the insect locomotion and fitness.…”
Section: Introductionmentioning
confidence: 99%
“…By examining several aspects of parasitoid oviposition behavior and reproductive success, this study shows that C. cephalonica is suitable as an alternative host for mass rearing of S. brevicornis. Dindo et al (2021) then investigated the efficacy of Monarda fistulosa L. (Lamiaceae) hydrolate as antimicrobial agent in artificial media for in vitro rearing of the parasitoid Exorista larvarum (L.) (Diptera: Tachinidae), as an alternative to the use of antibiotics (gentamicin). Although effective in controlling bacterial load, the M. fistulosa hydrolate supplemented to the artificial media significantly reduced E. larvarum development from the egg to the adult stage compared to gentamicin-supplemented medium, but not the number of eggs laid by the emerging females.…”
mentioning
confidence: 99%